2020
DOI: 10.1186/s41239-020-00232-z
|View full text |Cite
|
Sign up to set email alerts
|

Engagement in cloud-supported collaborative learning and student knowledge construction: a modeling study

Abstract: Many universities, especially in low-income countries, have considered the potential of cloud-supported collaborative learning in planning and managing students’ learning experiences. This is because cloud tools can offer students the necessary skills for collaboration with one another and improving communication between all users. This study examined how cloud tools can help students engage in reflective thinking, knowledge sharing, cognitive engagement, and cognitive presence experiences. The impact of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 55 publications
(46 reference statements)
0
37
0
1
Order By: Relevance
“…This step could help students get involved in the cognitive construction process, and improve the quality of the discussion. This process encourages students to relate their previous knowledge and experiences with the new questions, and thus gain new insights into the new situation (Baanqud et al, 2020). The previous study found that a group can think more creatively if individual members think independently before group discussion (Chen et al, 2021…”
Section: Curriculum Implementationmentioning
confidence: 98%
“…This step could help students get involved in the cognitive construction process, and improve the quality of the discussion. This process encourages students to relate their previous knowledge and experiences with the new questions, and thus gain new insights into the new situation (Baanqud et al, 2020). The previous study found that a group can think more creatively if individual members think independently before group discussion (Chen et al, 2021…”
Section: Curriculum Implementationmentioning
confidence: 98%
“…According to an extensive literature review, research in this field has generated considerable insights into the relationships between aspects of the learning environment and earning outcomes (Allen and Fraser, 2007). For example, research has shown that, in the online learning environment, instructors' use of cloud-supported collaborative tools is positively related to the development of learners' knowledge construction skills (Baanqud et al, 2020). The relationships between the learning environment and students' cognitive and affective outcomes, such as motivation, efficacy, and engagement (Allen and Fraser, 2007;Alqurashi, 2016;Xu et al, 2020), have become one of the most important lines of inquiry in studies of the learning environment.…”
Section: Literature Review the Role Of Instructors In The Online Learning Environmentmentioning
confidence: 99%
“…Synchronous online learning tools facilitating students' anonymous participation in activities and instructors' timely feedback, such as bullet subtitles and instant feedback on course content in Rain Classroom, have been widely used in higher education in mainland China since the outbreak of COVID-19. Researchers have suggested that scaffolding learning using cloud computing tools can develop learners' knowledge construction and mastery experiences (Azevedo et al, 2005;Baanqud et al, 2020), which are among the key sources of self-efficacy. The use of these scaffolding tools supports students' ASE in online learning by helping them to overcome anxiety and increasing their interaction and engagement with the course material.…”
Section: Ase As a Mediator Of The Relationships Between The Instructor's Role And Students' Perceived Learning Outcomes And Learning Satimentioning
confidence: 99%
See 1 more Smart Citation
“…In the classroom, instructors can scaffold this process by providing accessible collaboration tools, as learning to share information in the cloud prepares AEC students for professional practice [68]. The more participants share information, the more investment they have in the project and the more trust is extended, so practice in using collaboration platforms supports promotive interactions [69]. In addition, shared inter-team online collaborative workspaces allow mutual visibility not only of the team products but also of their work process.…”
Section: Recommendations For Shaping Effective Digitally-enabled Intementioning
confidence: 99%